Interferon α-2b spray shortened viral shedding time of SARS-CoV-2 Omicron variant: An open prospective cohort study - Xu, Nan; Pan, Jinjin; Sun, Li; Zhou, Cuimei; Huang, Siran; Chen, Mingwei; Zhang, Junfei; Zhu, Tiantian; Li, Jiabin; Zhang, Hong; Gao, Yufeng (Frontiers in Immunology, 2022)
Background: The Omicron SARS-CoV-2 variant has spread quickly worldwide due to its effects on virus transmission and vaccine effectiveness. Interferon(IFN) has been shown to have a protective effect against SARS-CoV because of its broad antiviral activity. This study aimed to analyze the treatment effects of IFN α-2b spray in virus clearance of the Omicron SARS-CoV-2 variant. Methods: We examined the effectiveness and safety of IFN α-2b spray in Shanghai, China, with participants infected with the Omicron SARS-CoV-2 variant in an open, prospective cohort study from April 16th to May 5th, 2022. Results: A total of 871 confirmed patients were enrolled in this study. Four hundred and thirteen patients were allocated to the IFN α-2b spray group, and 458 patients were allocated to the control group. The viral shedding time was significantly different between experimental group and control group (11.90 vs.12.58, P <0.05). In the experimental group, the median administration time since the first positive test for SARS-CoV-2 was three days, ranging from 0 to 15 days. There was no obvious adverse effect associated with the spray of IFN α-2b. The univariate Cox regression analysis revealed that the administration time since the first positive test ≤3 day was a protective factor associated with viral shedding time (HR 0.81 95% CI 0.74-0.87, P <0.05). Subgroup analysis showed that the viral shedding time was 10.41 (4.00-16.00) days in the ≤3 days group, which was significantly less than that in the control group (12.58, 95% CI: 7.00-19.15, P <0.0001) and in the >3 days group (13.56, 95%CI: 7.00-22.25, P <0.0001). Conclusions: IFN α-2b spray shortened the viral shedding time of the Omicron SARS-CoV-2 variant when administrated within three days since the first positive test for SARS-CoV-2.